2023
DOI: 10.20944/preprints202305.1420.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Efficient and Mild Method for the Alkylation of p-Cresol with tert-Butyl Alcohol

Abstract: The synthesis 2-tert-butyl-4-methylphenol is of great significance because of its widely application in industry, and the development of highly efficient catalyst is necessary to the alkylation of p-cresol and tert-butyl alcohol. Here, an efficient and mild method was established, caprolactam was chosen as hydrogen-bonding acceptor, p-toluenesulfonic acid was employed as hydrogen-bonding donor, and deep eutectic solvent (DES) was prepared to catalyze the alkylation reaction. The structure of the DES catalyst w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…On the other hand, to achieve satisfactory improvement in visual function, it is often necessary to undergo an extensive period of training (Herpich et al, 2019), which limits the application of VPL to some extent. Fortunately, research has demonstrated that NIBS not only directly improves visual perception (Battaglini et al, 2017;Reinhart et al, 2016) but also enhances VPL when combined with behavioral training (He et al, 2021;Wu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, to achieve satisfactory improvement in visual function, it is often necessary to undergo an extensive period of training (Herpich et al, 2019), which limits the application of VPL to some extent. Fortunately, research has demonstrated that NIBS not only directly improves visual perception (Battaglini et al, 2017;Reinhart et al, 2016) but also enhances VPL when combined with behavioral training (He et al, 2021;Wu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%